A test of a phenomenological model of size dependent melting in Au nanoparticles. (1st September 2017) - Dai, C.; Saidi, P.; Song, H.; Yao, Z.; Daymond, M.R.; Hoyt, J.J.
Abstract: It is well established that the melting point of a material decreases markedly as the system size approaches the nanoscale. However, despite over a century of study, the validity of any model for size dependent melting point depression has not been proven. In this work molecular dynamics simulations and a classical model of pure Au are used to perform a parameter free test of a phenomenological model of nanosphere melting. Consistent with model predictions, the simulations show that a premelted layer forms on the surface of the nanospheres at temperature well below the bulk melting point and the particle completely transforms to the liquid at a well defined instability temperature. The theoretical prediction of the instability temperature agrees very well with the simulation results, provided that the model is modified to include anisotropic surface properties. Graphical abstract: